Pengaruh Strategi Pembelajaran, Gaya Belajar, Disiplin Belajar, Lingkungan Keluarga Dan Fasilitas Belajar Di Sekolah Terhadap Prestasi Belajar Mata Pelajaran Ekonomi Kelas Xi Ips Di Sman 1 Sawahlunto - Maharani, Cici -; Wahyuni, Sri; Stevani, Stevani (Universitas PGRI Sumatera Barat, 2022)
Abstrack This study aims to analyze: 1) the influence of learning strategies on economic learning achievement of class XI social studies at SMA N 1 Sawahlunto, 2) the influence of learning styles on the achievement of learning economics class XI social studies at SMA N 1 Sawahlunto, 3) the influence of learning discipline on economic learning achievements of class XI social studies at SMA N 1 Sawahlunto, 4) the influence of the family environment on the achievement of learning economics class XI social studies at SMA N 1 Sawahlunto, 5) the influence of learning facilities on the achievement of learning economics class XI social studies at SMA N 1 Sawahlunto.This type of research is descriptive and associative. The population in this study was all students of class XI social studies at SMA N 1 Sawahlunto The sample was 51 people with a sampling technique in the form of proportional random sampling with the Slovin formula. The instruments used for this study were in the form of a closed questionnaire with multiple linear regression analysis tests and hypothesesy tests with t testsThe results of the study were (1) Based on the research, the results of learning strategies (X1) affected student learning achievement (Y) with a learning strategy regression coefficient value of 0.152 and a calculated value of 2.533> ttabel of 1.679 while the significance value of 0.015<005, means that Ha was accepted and H0 was rejected. (2) Based on the study, the results of the learning style (X2) affected student learning achievement (Y) with a learning style regression coefficient value of 0.237 and a calculated value of 2.943> ttabel of 1.679 while the significance value of 0.005<0.05, means that Ha was accepted and H0 was rejected. (3) Based on research, the results of learning discipline (X3) have an effect on student learning achievement (Y) with a learning discipline regression coefficient value of 0.098 and a calculated value of 2.071.071.> ttabel of 1.679 while the significance value of 0.044<005, means that Ha is accepted and H0 is rejected. . (4) Based on the research obtained, the results of the family environment (X4) affect student learning achievement (Y) with a family environment regression coefficient value of 0.096 and a calculated value of 2.302> ttabel of 1.679 while the significance value of 0.026<0.05, means ha is accepted and H0 is rejected. (5) Based on the research obtained, the results of learning facilities in schools (X5) affect student learning achievement (Y) with a regression coefficient value of learning facilities in schools of 0.080 and a calculated value of 2.090> ttabel of 1.679 while the significance value of 0.042<005, means ha is accepted and H0 is rejected. Keywords: Learning Strategies, Learning Styles, Learning Disciplines, Family Environment, Learning Facilities In Schools Towards Student Learning Achievement.